2015
DOI: 10.1523/jneurosci.2175-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Distributed and Dynamic Neural Encoding of Multiple Motion Directions of Transparently Moving Stimuli in Cortical Area MT

Abstract: Segmenting visual scenes into distinct objects and surfaces is a fundamental visual function. To better understand the underlying neural mechanism, we investigated how neurons in the middle temporal cortex (MT) of macaque monkeys represent overlapping random-dot stimuli moving transparently in slightly different directions. It has been shown that the neuronal response elicited by two stimuli approximately follows the average of the responses elicited by the constituent stimulus components presented alone. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(74 citation statements)
references
References 65 publications
4
69
1
Order By: Relevance
“…Procedures for surgical preparation and electrophysiological recordings were routine and similar to those described previously (Xiao et al, 2015). During sterile surgery with the animal under isoflurane anesthesia, a head post and recording cylinder were implanted to allow recording from neurons in cortical area MT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures for surgical preparation and electrophysiological recordings were routine and similar to those described previously (Xiao et al, 2015). During sterile surgery with the animal under isoflurane anesthesia, a head post and recording cylinder were implanted to allow recording from neurons in cortical area MT.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that the tuning curves of some MT neurons in response to overlapping bi-directional stimuli can show a directional "side-bias" toward one of the two direction components (Xiao and Huang, 2015). A subgroup of neurons prefers the stimulus component at the clockwise side of two motion directions, whereas another group of neurons prefers the component direction at the counter-clockwise side.…”
Section: Neurophysiological Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) The raster plot simulation generated based on the experiment. As shown in the raster plot, both directions affect the neuron spike frequency response [29]. (c) and (d) presents the simulation results from the number of misfiring before and after the frequency transition for both the Predictive Sliding Detection Window and the Charge and Fire protocols.…”
Section: Markov-chain Based Time-delay Patternsmentioning
confidence: 99%
“…The basic experimental fact relevant to our modeling project involves two sets of overlapping random dot stimuli moving in two separate directions [2]. Primate observers are able to segregate the two direction components and perceive motion transparency.…”
mentioning
confidence: 99%